Age and road safety performance: Focusing on elderly and young drivers. (October 2020) - Lyon, Craig; Mayhew, Dan; Granié, Marie-Axelle; Robertson, Robyn; Vanlaar, Ward; Woods-Fry, Heather; Thevenet, Chloé; Furian, Gerald; Soteropoulos, Aggelos
Abstract: The existing literature on young and elderly drivers indicates that they have the highest crash risks compared to other age groups of drivers. This study improves our understanding of the risk factors contributing to young and elderly drivers' elevated crash risk by examining self-report data from the E -Survey of Road User's Safety Attitudes (ESRA). The primary objective of this study is to compare the attitudes and behaviours of young, elderly, and middle-age drivers in Canada, the United States, and Europe. The main focus is on the practice of driving while distracted by mobile phones and driving while fatigued, as these are two dangerous behaviours that demonstrate the impact age may have. The analyses consistently showed that there are differences in the responses attributable to age. In all regions, drivers aged 18–21 years consistently reported higher rates of distracted and fatigued driving and higher rates of perceived social and personal acceptability of these behaviours than drivers aged 35–54 years. Elderly drivers aged 65+ years reported even lower rates of these behaviours and acceptability. Young drivers were also the least likely to believe that distraction and fatigue are frequent causes of road crashes, while elderly drivers were the most likely to believe this. This pattern with respect to age repeats in the support for policy measures as well; young drivers are least likely to support zero tolerance policies for mobile phone use when driving, while elderly drivers are the most likely to support this measure. Multivariate logistic regression modeling confirmed that elderly drivers were the least likely to engage in the use of mobile phones while driving or driving while fatigued. Statistically significant results showed that the middle-age group was less likely than young drivers to read a text message/email or check social media while driving and driving while fatigued. Highlights: Young drivers (18–21 years) reported higher rates of distracted and fatigued driving than middle-age drivers (35–54 years). Young drivers also showed higher rates of perceived social and personal acceptability of these behaviours. Elderly drivers (65+ years) reported even lower rates of these behaviours and acceptability. These trends are consistent across Canada, the United States, and Europe.